Perivascular Stromal Cells Instruct Glioblastoma Invasion, Proliferation, and Therapeutic Response within an Engineered Brain Perivascular Niche Model - Mai T. Ngo; Jann N. Sarkaria; Brendan A.C. Harley (Advanced Science, 2022)
Abstract Glioblastoma (GBM) tumor cells are found in the perivascular niche microenvironment and are believed to associate closely with the brain microvasculature. However, it is largely unknown how the resident cells of the perivascular niche, such as endothelial cells, pericytes, and astrocytes, influence GBM tumor cell behavior and disease progression. A 3D in vitro model of the brain perivascular niche developed by encapsulating brain‐derived endothelial cells, pericytes, and astrocytes in a gelatin hydrogel is described. It is shown that brain perivascular stromal cells, namely pericytes and astrocytes, contribute to vascular architecture and maturation. Cocultures of patient‐derived GBM tumor cells with brain microvascular cells are used to identify a role for pericytes and astrocytes in establishing a perivascular niche environment that modulates GBM cell invasion, proliferation, and therapeutic response. Engineered models provide unique insight regarding the spatial patterning of GBM cell phenotypes in response to a multicellular model of the perivascular niche. Critically, it is shown that engineered perivascular models provide an important resource to evaluate mechanisms by which intercellular interactions modulate GBM tumor cell behavior, drug response, and provide a framework to consider patient‐specific disease phenotypes.